Moved to Justice: The Effects of Socially Conscious Films on Social Justice Concerns. Issue 1 (2nd January 2021) - Khoo, Guan Soon; Ash, Erin
ABSTRACT: The unique blend of fun entertainment and social relevance in socially conscious films, e.g., Black Panther (2018), appeals to viewers' pleasure-seeking motives while it delivers social commentary. The present study examines the impact of pre-screening expectations and post-screening reflections on concerns for social justice. A two-stage 2 × 2 experiment was conducted to test the potential main effects and interactions of film expectations (socially conscious vs. fun expectations) and reflection (socially conscious vs. fun reflection) on social justice concerns, and meaningful affect. Results showed that socially conscious expectations increased social justice outcomes and meaningful affect. Mediation tests revealed that meaningful affect and threat-to-freedom explained the link between expectations and social justice concerns. Further, when conservative and some moderate viewers expect the film to be "socially important, " their perceptions of affirmative action policies become less negative. The present research provides initial evidence for the positive effects of popular, socially conscious films toward raising concerns for social justice.